Identification and Assessment of Supply Chain Risks Associated with Dairy Products Sector - Muhammad Zubair ,; Nadeem Ahmad Mufti, (Journal of Basic & Applied Sciences, 2015)
Risks cannot be entirely removed or eliminated from Human’s life and from lives of Organizations but may be mitigated and their effects may be reduced. The principal objective of this research is to identify and assess supply chain risks in dairy products sector. A set of supply chain risks is identified through extensive literature survey and is divided into five major categories and 28 components through Risk Breakdown Structure approach. A questionnaire is developed based upon these 28 components and data collected from 170 respondents. Risks are assessed through Probability and Impact scores obtained from responses and then slotted into 2x2 Risk Matrix. A risk matrix comprising of 04 quadrants is formulated through low and high scores of probability and impact of all 28 risks. It is found that 16 risks fall in high risk quadrant, 08 in moderate and 04 in low risk quadrant. Risks of competition, deceases, terrorism, quality of raw materials, natural disasters along with those falling high risk quadrants are required to be promptly responded by dairy sector operators for effective risk mitigation. Similarly risk responses have been suggested for moderate and low gravity risks as well.